Odpowiedzi

2010-03-10T13:50:19+01:00
I=U/R
U=I*R
R=I/U

P=F/S
F=P*S
S=P/F

d=m/v
m=d*v
v=m/d

C=5R/2M
R=(c*2M)/5
M=10R/C
2010-03-10T13:52:31+01:00
I=U/R
wyznaczam U:
I=U/R I*R (mnożę obie srtony przez R
IR=U

Wyznaczam R:
I=U/R I*R
IR=U I:I (dzielę przez I)
R=U/I

p=F/S
F=?

p=F/S I*S
PS=F

S=?
p=F/S I*S
pS=F I:p
S=F/p

d=m/v
m=?

d=m/v I*v
dv=m

v=?
d=m/v I*v
dv=m I:d
v=m/d



c=5R/2M
R=?
c=5R/2M I*2M
2Mc=5R I:5
R=2Mc/5

M=?
c=5R/2M I*2M
2cM=5R I:2c
M=5R/2c
2010-03-10T13:59:49+01:00
U/R=I/*R U/R=I/:U
U=I*R R=I/U

F/S=p/ *s F/S=p/:F
F=p*S S=p/F

m/v=d/*v m/v=d/:v
m=d*v dv=m/:d
v=m/d

5R/2M=c/*2M 5R/2M=c/*2M
5R=2Mc/:5 2Mc=5R/2c
R=(2m*c):5 M=5R/2c